Cancer in pregnancy: safety and efficacy of systemic therapies. Issue 5 (September 2017) - Boere, Ingrid; Lok, Christianne; Vandenbroucke, Tineke; Amant, Frédéric
Abstract : Purpose of review: Cancer in pregnancy has become increasingly frequent. It has become clear that for specific cancers under well defined circumstances, oncological treatment in pregnancy can be well tolerated and feasible for both mother and fetus. Continued critical assessment of the available literature and registration of cancer in pregnancy cases and outcomes for mother and child are necessary to work toward implementing optimal cancer treatment during pregnancy. Recent findings: Physiologic changes in pregnancy may alter distribution and efficacy of systemic therapy. Data on systemic therapy including, chemotherapy, hormonal therapy, and targeted therapy during pregnancy are available but incomplete. Outcomes of fetuses exposed to chemotherapy in utero are generally reassuring, but new targeted therapies are mostly discouraged in pregnancy. Summary: Cancer treatment during pregnancy is possible, depending on type and timing of systemic therapy and treatment modality. Available data are reassuring with a modest increase in complications such as growth restriction and preterm birth. The effect of new targeted therapies is often still unclear and therefore discouraged.